Ultrasound‐Assisted Synthesis of Nitrogen and Oxygen Containing Heterocycles Using Fluorinated Graphene Oxide as Catalyst: Evaluation of Their Anthelmintic Activities. Issue 25 (2nd July 2020) - Dutta, Arup; Chhetri, Bhusan; Nongrum, Ridaphun; Kupar Kharmawlong, George; Yadav, Arun K.; Nongkhlaw, Rishanlang
Abstract: Spirooxindole derivatives have been efficiently synthesized via a three‐component reaction consisting of isatin, malononitrile/ pyrazole and various 1, 3‐diketones using Fluorinated Graphene Oxide (FGO ) as a green and metal free carbocatalyst, under sonication. The main advantages of this synthetic approach lie in its operational simplicity, easy catalyst recovery and recyclability, high yields and short reaction times. The prepared catalyst was characterized by various analytical techniques viz ., UV‐Vis, FT‐IR Spectroscopy, TGA, TEM, FE‐SEM and EDX . The in vitro anthelmintic screening of synthesized compounds against a cestode, Raillietina sp. and a nematode parasite, Syphacia obvelata at 200 μg/mL and 800 μg/mL were also carried out which revealed a profound activity, with much reduced morality time of parasite. The SEM study indicated structure alterations in treated parasite, further validating the in vitro anthelmintic property. In addition, molecular docking studies were carried out against β‐tubulin protein to determine binding affinity of the synthesized compounds. All test compound followed the "Lipinski Rule of Five" and in silico pharmacokinetic investigation showed inhibitory activity against CYP enzyme and P‐glycoprotein which may further improve the bio efficacy of compounds. Abstract : The green and metal free carbocatalyst, Fluorinated Graphene Oxide (FGO ) was prepared and characterized by various analytical techniques. The catalytic activity of the prepared catalyst was efficiently employed for the synthesis of nitrogen and oxygen containing spiro heterocycles. The main advantages of this synthetic approach lie in its operational simplicity, high yields, easy catalyst recyclability, eco‐friendly procedures and short reaction times. The in vitro anthelmintic screening of synthesized compounds against a cestode and a nematode parasite has been carried out.